Investigating University Students’ and Lecturers’ Anxiety in the AI-Laden English Online Learning - Santosa, Made Hery (Jurnal Pendidikan dan Pengajaran, 2025)
The integration of AI-driven digital tools in online English instruction presents unique anxiety challenges for both students and lecturers, particularly in non-native English contexts. This study explores anxiety levels among university students and lecturers engaged in AI-assisted English learning in North Bali. Employing an explanatory sequential mixed-methods design, data were collected from 220 students and 20 lecturers using the Foreign Language Classroom Anxiety Scale (FLCAS) questionnaire and semi-structured interviews with five students and two lecturers. Quantitative data were analyzed using SPSS for frequency distributions, categorized using Oetting’s Scale, while qualitative data were examined through thematic analysis. Results indicated that students experienced mild anxiety, particularly during assessments, due to test-related stress, connectivity issues, and limited access to digital tools. Lecturers, however, exhibited higher anxiety levels, primarily stemming from digital skill gaps and challenges in assessing AI-generated student work. These findings highlight the urgent need for institutional policies that address digital literacy gaps, clearer assessment guidelines, and targeted professional development programs. Additionally, psychological support initiatives can help both students and lecturers manage anxiety effectively. By fostering a supportive and well-prepared educational environment, institutions can enhance digital readiness and reduce anxiety in AI-integrated English learning settings.